PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN KONSUMEN DI HOTEL SUMBER RIA KOTA GORONTALO - Rosmina Hiola (Jurnal Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to know and analyze the influence of service marketing mix to customer satisfaction at Sumber Ria Hotel Gorontalo City. Either simultaneously or partially. The analytical method used is path analysis or path analysis. Based on the results of this study, the first hypothesis proposed said that the Variables of Service Marketing Mix consisting of People (X1), Physical Evident (X2), Process (X3) simultaneously have a positive and significant effect on customer satisfaction at Hotel Sumber Ria Kota Gorontalo. The second hypothesis that People Variables (X1) partially have a positive and significant impact on customer satisfaction in Hotel Sumber Ria Kota Gorontalo. The third hypothesis that Physical Evident Variables (X2) partially have a positive and significant impact on customer satisfaction at Hotel Sumber Ria Kota Gorontalo. The fourth hypothesis that Process Variables (X3) partially have a positive and significant impact on customer satisfaction at Sumber Ria Hotel Gorontalo.